Exploring the anticancer mechanism of cardiac glycosides using proteome integral solubility alteration approach - Wenjie Qin; Yinhua Deng; Huan Ren; Yanling Liu; Ling Liu; Wenhui Liu; Yuxi Zhao; Chen Li; Zhiling Yang (Cancer Medicine)
Abstract Background and Aims Cardiac glycosides (CGs), traditionally used for heart failure, have shown potential as anti‐cancer agents. This study aims to explore their multifaceted mechanisms in cancer cell biology using proteome integral solubility alteration (PISA), focusing on the interaction with key proteins implicated in cellular metabolism and mitochondrial function. Methods We conducted lysate‐based and intact‐cell PISA assays on cancer cells treated with CGs (Digoxin, Digitoxin, Ouabain) to analyze protein solubility changes. This was followed by mass spectrometric analysis and bioinformatics to identify differentially soluble proteins (DSPs). Molecular docking simulations were performed to predict protein‐CG interactions. Public data including gene expression changes upon CG treatment were re‐analyzed for validation. Results The PISA assays revealed CGs’ broad‐spectrum interactions, particularly affecting proteins like PKM2, ANXA2, SLC16A1, GOT2 and GLUD1. Molecular docking confirmed stable interactions between CGs and these DSPs. Re‐analysis of public data supported the impact of CGs on cancer metabolism and cell signaling pathways. Conclusion Our findings suggest that CGs could be repurposed for cancer therapy by modulating cellular processes. The PISA data provide insights into the polypharmacological effects of CGs, warranting further exploration of their mechanisms and clinical potential.